2017
DOI: 10.1055/s-0043-117612
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilus Delbrueckii subsp. Bulgaricus Modulates the Secretion of Th1/Th2 and Treg Cell-Related Cytokines by PBMCs from Patients with Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is an inflammatory skin disease which may be due to the imbalance between Th1-, Th2 and Treg cell-related immune responses. Evidences suggest that appropriate stimulation with probiotics may correct the skewed immune response in children with AD. The aim was to determine the effects of the yogurt culture on the secretion of Th1/Th2/Treg type cytokines by PBMCs from children with AD. was cultivated on MRS broth. The PBMCs from 20 children with AD were separated by Ficoll-Hypaque centrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
11
1
2
Order By: Relevance
“…Probiotic bacteria regulate mucosal immune responses through the induction of different cytokines. This effect is dependent on the probiotic strain itself [67][68][69]. After oral probiotic administration, cytokines produced by T cells in the lamina propria of the small intestine were secreted in slightly higher levels than those observed in the presence of commensal bacteria; specifically IFN-γ and TNF-α cytokines [70][71][72][73].…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 99%
“…Probiotic bacteria regulate mucosal immune responses through the induction of different cytokines. This effect is dependent on the probiotic strain itself [67][68][69]. After oral probiotic administration, cytokines produced by T cells in the lamina propria of the small intestine were secreted in slightly higher levels than those observed in the presence of commensal bacteria; specifically IFN-γ and TNF-α cytokines [70][71][72][73].…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 99%
“…The pathology of AD is accompanied by an imbalance in immunity involving Th1, Th2, and Treg cells, culminating in alterations in Th1-and Th2-mediated immune responses and IgE-mediated hypersensitivity [31]. The expression levels of the Th2 cytokines IL-4 and IL-13 are elevated in AD lesions.…”
Section: Immune Dysfunction In Atopic Dermatitismentioning
confidence: 99%
“…They found that L. delbrueckii subsp. bulgaricus could modulate the secretion of Th1- and Th2-Treg-related cytokines in AD patients [113]. In addition to Th1- and Th2-Treg-related cytokines, Rø et al found that perinatal maternal probiotic supplementation with a combination of LGG, B. animalis subsp.…”
Section: Efficacy and Safety Of Probiotics And Fmt In Clinical Trimentioning
confidence: 99%